MEKTEP KURSÍNDAǴÍ VEKTOR TEMASÍNDA QOLLANÍW MÚMKIN BOLǴAN METODLAR - Tanirbergenov, Sadıq Aleuovich; Abdieva, Gulmira Kojamuratovna (SCIENCE and SOCIETY, 2026)
This article presents methods for teaching students the vector system studied in a school geometry course. It demonstrates ways to convey the concept of vectors to students through various games.